2021
DOI: 10.15252/emmm.202013258
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative VPS41 variants inhibit HOPS function and mTORC1‐dependent TFEB/TFE3 regulation

Abstract: Vacuolar protein sorting 41 (VPS41) is as part of the Homotypic fusion and Protein Sorting (HOPS) complex required for lysosomal fusion events and, independent of HOPS, for regulated secretion. Here, we report three patients with compound heterozygous mutations in VPS41 (VPS41S285P and VPS41R662*; VPS41c.1423‐2A>G and VPS41R662*) displaying neurodegeneration with ataxia and dystonia. Cellular consequences were investigated in patient fibroblasts and VPS41‐depleted HeLa cells. All mutants prevented formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 89 publications
4
33
0
Order By: Relevance
“…Recent studies reported the presence of loss-of-function mutations in the genes encoding the subunits of the HOPS complex, in particular VPS41 and VPS16, in patients with severe neurological impairment [89,90]. Loss of VPS41 was associated with constitutive nuclear localization of TFE3, even though the phosphorylation of S6K and 4E-BP1 was not altered [89]. These findings strongly suggest that dysfunction of the HOPS complex can specifically affect the non-canonical mTORC1 signaling axis.…”
Section: Trends Trends In In Cell Biologymentioning
confidence: 88%
See 1 more Smart Citation
“…Recent studies reported the presence of loss-of-function mutations in the genes encoding the subunits of the HOPS complex, in particular VPS41 and VPS16, in patients with severe neurological impairment [89,90]. Loss of VPS41 was associated with constitutive nuclear localization of TFE3, even though the phosphorylation of S6K and 4E-BP1 was not altered [89]. These findings strongly suggest that dysfunction of the HOPS complex can specifically affect the non-canonical mTORC1 signaling axis.…”
Section: Trends Trends In In Cell Biologymentioning
confidence: 88%
“…Mutations in the homotypic fusion and vacuole protein sorting (HOPS) complex The HOPS complex is a multi-subunit tethering complex which plays a crucial role in the fusion of lysosomes with late endosomes and autophagosomes [88]. Recent studies reported the presence of loss-of-function mutations in the genes encoding the subunits of the HOPS complex, in particular VPS41 and VPS16, in patients with severe neurological impairment [89,90]. Loss of VPS41 was associated with constitutive nuclear localization of TFE3, even though the phosphorylation of S6K and 4E-BP1 was not altered [89].…”
Section: Trends Trends In In Cell Biologymentioning
confidence: 99%
“…As human genomic data flood the present research landscape with tantalizing associations and clues to disease mechanisms, the challenging task to functionally annotate these genomic variants has become increasingly significant. Research consortia have arisen to tackle the challenges of rare and undiagnosed diseases (57,58,59), joining the efforts of individual labs in parsing the data deluge with experimentation to accelerate therapeutic target and drug discovery for more common diseases as well (37,(60)(61)(62)(63). These collective efforts have begun to bear fruit, and they are not limited to the direct relationship between genotype and phenotype alone.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the functional duality represented by TNK2/SID-3 axis in the coordination of both dopamine and dsRNA import into the dopaminergic neurons of C. elegans warrants further mechanistic investigation. We previously established C. elegans as a genetic animal model with which to investigate and reveal numerous conserved genes and cellular pathways underlying progressive dopaminergic neurodegeneration, often predating their association to PD in humans (9,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). A distinct advantage of this model is the capacity to rapidly quantify dopaminergic neurodegeneration with precision, at the single-neuron level, and with rigor across large isogenic populations of animals per experiment (38,39).…”
Section: Introductionmentioning
confidence: 99%
“…For example, patients mutated in VPS11 present with signs of hypomyelination that can be associated with leukoencephalopathy [138][139][140][141]. Mutations in VPS11 could also give rise to dystonia as observed in patients mutated in VPS16 and VPS41, associated with ataxia for the latter [141][142][143][144][145][146]. Of note, mutations in SNAP29 are also involved in neurological disorders since they can lead to the development of the cerebral dysgenesis, neuropathy, ichthyosis, and keratoderma (CEDNIK) syndrome [147][148][149].…”
Section: Autophagosome-lysosome Fusionmentioning
confidence: 99%